Zinc Oxide Doped with Chlorine: Synthesis, Characterization, and \(α\)-Amylase Inhibitors - A. A. Al-Arfaj; Soheir N. Abd El-Rahman (Current Topics on Chemistry and Biochemistry Vol. 5, 2022)
In the present study, we prepared Zinc Oxide nanoparticles (ZnONPs) and Zinc Oxide nanoparticles doped with Chlorine (Cl: ZnONPs) by chemical solution method from zinc acetate (ZnAc) and oxalic acid (OX. acid). The characterization of ZnONPs and Cl: ZnONPs were determined by FTIR, X-ray, SEM, and TEM. Also, ZnONPs and Cl: ZnONPs \(α\)-amylase inhibitors were determined. The results of SEM indicated that the average particle size of ZnONPs and Cl: ZnONPs are 46.65-74.64 nm. ZnONPs and Cl: ZnONPs TEM images showed a round shape. The compounds b-d and e gave highly significant inhibitory activity against the \(α\)-amylase enzyme and were very close to that of acarbose, thereby, projecting ZnONPs and Cl: ZnONPs as \(α\)-amylase inhibitors.